Zielinski and Homeric Suspense (Circe de clásicos y modernos, 2023)
This article aims to explain why in Homeric narrativity, where usually nothing happens in the background, there is no suspense linked to an uncertainty about an outcome; it will link this to the so-called “Zielinski’s law” (I). It will also analyse recent attempts to find suspense gaps in Homer (II). Finally, it will advance an alternative explanation for suspense, based on empathy for a given character and immersion in the narrative world (III).
Keywords: Homer; narratology; suspense; Zielinski; Sternberg